2008
DOI: 10.1002/art.23471
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic progression of ankylosing spondylitis after up to two years of treatment with etanercept

Abstract: Objective. To investigate the effect of etanercept therapy on radiographic progression in patients with ankylosing spondylitis (AS).Methods Conclusion. Unlike other inflammatory rheumatic diseases such as rheumatoid arthritis and psoriatic arthritis, structural progression in AS seems to be independent of TNF, despite the fact that TNF is responsible for the signs and symptoms due to inflammation in this disease.Ankylosing spondylitis (AS) belongs to a family of rheumatic diseases known as spondylarthritides t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
229
3
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(258 citation statements)
references
References 31 publications
15
229
3
11
Order By: Relevance
“…However, because it is not feasible to conduct a placebo-controlled study over 2 years, patients from the long-term observational cohort of the Outcome Assessments in Ankylosing Spondylitis International Study (OASIS), which was started in the 1990s, were used as the control group. The results of both studies, reported thus far in abstract form, have indicated that there was no significant difference in the mean score for radiographic progression between the groups treated with the TNF blockers etanercept (11) or infliximab (12) and the control group. Interestingly, in both studies, there was a small but nonsignificant tendency for less radiographic progression in the patients treated with TNF blockers when their scores were compared with only those in the subgroup of OASIS patients who met the eligibility criteria for inclusion in the TNF blocker trials.…”
Section: Effect Of Tnf Blockers On Structural Damage In Asmentioning
confidence: 90%
See 1 more Smart Citation
“…However, because it is not feasible to conduct a placebo-controlled study over 2 years, patients from the long-term observational cohort of the Outcome Assessments in Ankylosing Spondylitis International Study (OASIS), which was started in the 1990s, were used as the control group. The results of both studies, reported thus far in abstract form, have indicated that there was no significant difference in the mean score for radiographic progression between the groups treated with the TNF blockers etanercept (11) or infliximab (12) and the control group. Interestingly, in both studies, there was a small but nonsignificant tendency for less radiographic progression in the patients treated with TNF blockers when their scores were compared with only those in the subgroup of OASIS patients who met the eligibility criteria for inclusion in the TNF blocker trials.…”
Section: Effect Of Tnf Blockers On Structural Damage In Asmentioning
confidence: 90%
“…Therefore, in 2 trials of TNF blockers, the baseline score was compared with the score after 2 years of treatment (11,12). However, because it is not feasible to conduct a placebo-controlled study over 2 years, patients from the long-term observational cohort of the Outcome Assessments in Ankylosing Spondylitis International Study (OASIS), which was started in the 1990s, were used as the control group.…”
Section: Effect Of Tnf Blockers On Structural Damage In Asmentioning
confidence: 99%
“…An alternative hypothesis was then proposed whereby pathogenetic factors such as altered gene expression, biomechanical factors, and bacteria trigger the concomitant expression of inflammation and new bone formation, which then proceed along essentially autonomous pathways (2). This hypothesis has been advanced to explain the apparent lack of benefit of anti-TNF␣ agents on the radiographic progression of AS (3)(4)(5).…”
mentioning
confidence: 99%
“…The goal of treatment of axial SpA is to obtain the suppression of symptoms but also the prevention of structural bone damage and of ankylosis. The studies on anti-TNF agents in longstanding axial disease have demonstrated that the structural damaged cannot be prevented and that it is independent from the presence of absence of inflammatory activity (13)(14)(15). A great effort should be done to increase the referral of every axial SpA patient to the rheumatologist.…”
mentioning
confidence: 99%